Web-Based Parent Training Intervention With Telephone Coaching for Disruptive Behavior in 4-Year-Old Children in Real-World Practice: Implementation Study - Ristkari T; Kurki M; Suominen A; Gilbert S; Sinokki A; Kinnunen M; Huttunen J; McGrath P; Sourander A (JMIR PUBLICATIONS, INC, 2022)
Background: Parent training is the most effective approach to the psychosocial treatment of disruptive behavioral problems in childhood. However, no studies exist on how well Web-based training programs work when they make the transition from the research setting to implementation in primary health care.
Objective: The study aimed to examine how the randomized controlled trial (RCT) and implementation study groups of the Strongest Families Smart Website (SFSW) intervention differed in child psychopathology, family demographics and treatment-related factors, such as therapeutic alliance and parents' satisfaction rates. The intervention was conducted in the pediatric primary health care in Finland.
Methods: The study focused on 232 parents who had taken part in the SFSW intervention, which formed part of a 2-arm RCT study, and 882 families that would participate in the subsequent SFSW implementation study group. Both groups comprised parents whose children displayed high levels of parent-reported disruptive behavioral problems when they were screened in child health clinics at 4 years of age. Parents in both groups were provided with the SFSW intervention, which consisted of a Web-based training program with 11 weekly themes and associated telephone sessions.
Results: Demographic factors or duration of behavioral problems did not differ statistically or clinically between the RCT and implementation groups. Overall, 42.0% (362/862) of children in the implementation group and 35.4% (80/226) in the RCT intervention group had suffered from behavioral difficulties more than 1 year before the screening phase (chi(2)(1)=3.2; P=.07). The mean duration of telephone coaching calls was very similar in the implementation and RCT intervention groups, that is, 38 and 37 min per call, respectively (t(279.5)=0.26; P=.79). The total time spent on the website of the program was 451 min in the implementation group and 431 min in the RCT intervention group (t(318.8)=1.38; P=.17). In the RCT intervention group, 52 of the 232 participants (22.4%) discontinued the program before the tenth week, whereas in the implementation group, 109 of the 882 participants (12.4%; odds ratio 2.05, 95% CI 1.4-3.0; P<.001) discontinued. Parents in both the implementation (77.1% to 98.5%, 498/742 to 731/742, respectively) and the RCT (64.8% to 98.2%, N=105/162- to 159/162, respectively) groups reported qualitatively similar and high level of posttreatment satisfaction rates in improved parenting skills, expectations, and stress relief. Parents in both groups reported a high level of satisfaction in skills and professionalism of the telephone coaches.
Conclusions: The implementation of population-based screening of Web-based parent training intervention with telephone coaching resulted in good feasibility, fidelity, accessibility, and similar satisfaction level post treatment when compared with intervention in RCT research setting. The discontinuation of treatment in the implementation group was exceptionally low.